APPLICATION OF IMAGE ANALYSIS METHODS FOR ISOCENTER QUALITY ASSURANCE IN RADIOTHERAPY - Niedźwiecki, Michał; Tomaszuk, Monika; Kabat, Damian; Latała, Zbigniew; Rzecki, Krzysztof; Tabor, Zbislaw (Image Analysis and Stereology, 2017)
One of the major procedures for testing the geometrical accuracy of devices used in radiotherapy treatments is the test of the geometrical position of the radiation isocenter. The importance of the test reflects the fact that geometrical position of the radiation isocenter generally affects the tumor targeting. At present the geometric accuracy is assessed with the Winston-Lutz test which checks the position of an image of a ball marker with the respect to the center of the radiation field as projected on a detector plane. Obviously, determination of coordinates of a single marker is not sufficient to fully account for a complicated geometry of a therapeutic device. The purpose of the study was to design a new image analysis tool to better determine the isocenter. The proposed automated procedure for determining isocenter position uses projection data acquired for a special cube phantom. The projection images of a phantom are acquired for various angles of rotation of the gantry. A procedure is proposed to extract some geometric characteristics of a therapeutic device from the projection images.